2016
DOI: 10.2217/fmb.15.142
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Inactivation of Candida Albicans by Hematoporphyrin Monomethyl Ether

Abstract: Candida albicans can be effectively inactivated by HMME in the presence of light, and HMME-mediated PACT shows its potential as an antifungal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…The TEM samples were prepared according to a previously described method. 28 In brief, microconidia of T rubrum were treated with HMME-mediated aPDT and collected by centrifugation at 3500 rpm for 10 minutes. Next, 2.5% glutaraldehyde was added, and the microconidia were incubated at 4°C for 2 hours.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
See 3 more Smart Citations
“…The TEM samples were prepared according to a previously described method. 28 In brief, microconidia of T rubrum were treated with HMME-mediated aPDT and collected by centrifugation at 3500 rpm for 10 minutes. Next, 2.5% glutaraldehyde was added, and the microconidia were incubated at 4°C for 2 hours.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…[24][25][26] In our previous studies, it was found that HMME-mediated aPDT could inactivate several important gram-positive and gram-negative antibiotic-resistant bacteria and Candida albicans in planktonic condition and biofilms. [27][28][29] However, the photodynamic inactivation (PDI) efficacy and effects of HMME-mediated aPDT on dermatophyte fungi remain unclear. Therefore, in this study, we have assessed the potential of HMME to mediate photodynamic treatment against T rubrum and evaluated its effects on cellular structure in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, HMME is less costly than other photoactive drugs . In our previous study, we found that HMME was effective at killing C. albicans cells in planktonic suspensions in the presence of light . The aim of the present work was to assess the PDI efficacy of HMME for the biofilms produced by standard and fluconazole‐resistant C. albicans strains.…”
Section: Introductionmentioning
confidence: 97%